The Role of Environmental, Social, and Governance (ESG) Accounting Disclosure in Enhancing Tax Planning and Corporate Governance: An Applied Study on Industrial Sector Companies in Salah Al-Din Governorate - Yousif Hameed Nayyef (Academia Open, 2026)
General Background: Environmental, Social, and Governance (ESG) accounting disclosure has become a central component in promoting transparency, sustainability, and responsible corporate practices in modern business environments. Specific Background: Industrial companies in Salah al-Din Governorate face increasing challenges related to weak governance practices, limited transparency, and inefficient tax planning, while ESG disclosure remains underutilized. Knowledge Gap: Despite growing global attention to ESG practices, there is limited empirical evidence on their integration with tax planning and corporate governance in emerging economies, particularly within Iraq’s industrial sector. Aims: This study aims to examine the role of ESG accounting disclosure in improving tax planning and corporate governance practices among industrial companies in Salah al-Din Governorate. Results: Using a descriptive-analytical approach and field survey data from 52 companies analyzed through SPSS, the findings indicate a statistically significant positive relationship between ESG disclosure and both tax planning and governance quality (R²=0.51). Social disclosure shows the strongest correlation (r=0.74), followed by environmental disclosure (r=0.68) and governance disclosure (r=0.65). Novelty: The study provides empirical evidence linking ESG disclosure with tax planning and governance within an emerging industrial context. Implications: The findings highlight the need for a national regulatory framework, improved disclosure infrastructure, and increased awareness to support sustainable reporting and strengthen governance and tax planning practices. Highlights:• Strong Statistical Relationship Identified Between Sustainability Reporting and Decision Quality• Social Dimension Shows Highest Correlation With Reputation and Regulatory Risk Reduction• Low Adoption Levels Indicate Structural Barriers in Reporting Practices Keywords: ESG Disclosure, Tax Planning, Corporate Governance, Industrial Companies, Sustainability Reporting.